2001
DOI: 10.1074/jbc.m009030200
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Expression, and Substrate Specificity of a Mammalian β-Carotene 15,15′-Dioxygenase

Abstract: We have identified from mouse the first mammalian ␤-carotene 15,15-dioxygenase (␤-CD), a crucial enzyme in development and metabolism that governs the de novo entry of vitamin A from plant-derived precursors. ␤-CD is related to the retinal pigment epithelium-expressed protein RPE65 and belongs to a diverse family that includes the plant 9-cis-epoxycarotenoid dioxygenase and bacterial lignostilbene dioxygenases. ␤-CD expression in Escherichia coli cells engineered to produce ␤-carotene led to the accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
225
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(231 citation statements)
references
References 37 publications
(39 reference statements)
5
225
0
Order By: Relevance
“…The requirement of ␤-carotene as the C 40 carotenoid acted on by the NinaB BCO is suggested by the observation that bacterially expressed NinaB BCO does not process zeaxanthin or other hydroxylated C 40 carotenoids to the C 20 3-OH retinal (26). Similar specificity was observed for mammalian BCO homologs (12,13). If Drosophila in vivo conditions of NinaB BCO activity are the same, the successful use of zeaxanthin or lutein (16) as a dietary source for the 3-OH retinal requires that these hydroxylated C 40 carotenoids are first converted to ␤-carotene.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The requirement of ␤-carotene as the C 40 carotenoid acted on by the NinaB BCO is suggested by the observation that bacterially expressed NinaB BCO does not process zeaxanthin or other hydroxylated C 40 carotenoids to the C 20 3-OH retinal (26). Similar specificity was observed for mammalian BCO homologs (12,13). If Drosophila in vivo conditions of NinaB BCO activity are the same, the successful use of zeaxanthin or lutein (16) as a dietary source for the 3-OH retinal requires that these hydroxylated C 40 carotenoids are first converted to ␤-carotene.…”
Section: Discussionsupporting
confidence: 48%
“…The availability of vitamin A for metabolic processes is governed by multiple factors, including dietary absorption, transport, metabolism, and storage (11). A human BCO is expressed in the retinal pigment epithelium and also in the kidney, intestine, liver, brain, stomach, and testis (12,13), suggesting that the processing of dietary carotenoids occurs in a variety of vertebrate tissues. Additional studies show that centric cleavage of ␤-carotene plays a major role in the processing of carotenoids (14,15).…”
mentioning
confidence: 99%
“…Although beta-carotene cleavage activity was demonstrated in cell-free extracts derived from mammalian small intestine in the 1960s, purification of the enzyme proved surprisingly challenging [47][48][49][50]. It was not until the advent of molecular biological approaches and mass spectral sequencing that the beta-carotene cleavage enzyme was cloned first from Drosophila and chicken and later from humans [54][55][56][57][58]. It is a cytosolic enzyme primarily localized in the duodenal mucosa although it has been found in liver and in the eye.…”
Section: Carotenoid Metabolic Enzymesmentioning
confidence: 99%
“…It has been demonstrated that this enzyme can act on other carotenoids also; however, provitamin A activity might vary depending on the substrate. Cloning of mammalian proteins similar to the 15, 15′ β-carotene oxygenase has revealed the existence of RPE65 [54,56], a protein critical to the cis-trans isomerization of retinoids in the visual cycle, as well as an enzyme that catalyzes the asymmetric cleavage of beta-carotene at the 9′-10′ position [47][48][49]57].…”
Section: Carotenoid Metabolic Enzymesmentioning
confidence: 99%
“…Alternatively, because it belongs to a family of carotenoid oxygenases, RPE65 may play a direct catalytic role in the visual cycle. This family, including bacterial (22), plant (23), invertebrate (24), and vertebrate (25,26) carotenoid oxygenases, shares four absolutely conserved histidines that coordinate the iron required for activity of these enzymes (22,27). Because RPE65 retains these histidines, it might also bind catalytic iron to play a role in isomerization.…”
mentioning
confidence: 99%